Medical Aspects Biomechanics and Muscle Motor Activity in Kettlebell Snatch: Review - A. S. Dobrovolski; O. V. Galuschenko (Медицинский вестник Юга России, 2012)
Review summarizes the medical aspects of the biomechanics and muscle motor activity in handlebell sport on an example of cyclic exercise “kettlebell snatch”. Performed the comparative analysis of different techniques of performance of kettlebell snatch. Provides information about of the kettlebell exercises and recommendation of the Russian and foreign authors for strengthening of stabilizing muscles, preventive maintenance of the musculoskeletal disorders.